Diseño y creación de un portal web para la internacionalización del banano Cavendish por la cooperativa de agricultores de Colombia de Guacamayal- Coopracol (2022)
Currently, the Covid-19 pandemic has made us change the way we work, reinvent ourselves and that is why this business plan aims to determine the economic viability of digitally transforming the Guacamayal Cooperative of Farmers of Colombia - COOPRACOL in the commercialization of Products such as Cavendish Bananas, through electronic commerce, which consists of the purchase and sale of products through electronic means such as the Internet or other computer networks, which today constitutes a business model disruptive innovator of utmost importance with our national and international community and more at times when companies significantly seek cost reduction, efficient services, product quality, environmental protection and teleworking, in which the use of the new alternatives and supported business models of E-commerce becomes an important reason in the search of national and international markets based on technology 4.0, internet of things, artificial intelligence and cybersecurity. A strategic analysis will be carried out with the companies of its competence and the current situation of their business models implemented through internationalization.